Abandoning Either/Ors in Analyzing Shifts in Humanitarian Reporting. (2nd January 2020) - Nolan, David; Brookes, Stephanie; Imison, Michelle
ABSTRACT: The shifting constitution of journalists as humanitarian actors has profound implications for changing forms of journalism practice, as well as for the normative models through which journalists understand and reflect on that practice. In an effort to develop a more empirically-grounded engagement with change, this article explores the interview testimonies of Australian journalists who cover international and humanitarian issues. It argues that frameworks reliant on stark oppositions (between past and present, optimism and pessimism, or moral agency and material structure) are both empirically and practically problematic, and seeks to move beyond these. Engagement with data from semi-structured interviews offers insight into how journalists' perceptions of and responses to change are shaped by the historical and shifting institutional relations in which they are implicated.